Kesesuaian Sistem Pengawasan Perizinan Berbasis Risiko di Sektor Lingkungan Hidup Pasca UU Cipta Kerja Dengan Prinsip Perlindungan dan Pengelolaan Lingkungan Hidup di Indonesia - Eko Prasetyo (Fakultas Hukum Universitas Islam Indonesia, 2024)
Cipta Kerja Act brings significant changes to the model of Business Licensing Supervision. However, there are concerns about the compatibility of this system with protection principles. Using a juridical-normative research method, this article identifies that environmental management and protection in Indonesia apply the principles of precaution, prevention, and sustainability. Furthermore, the detailed supervisory system established under the Business Licensing regime tends to be more effective compared to the previous system. Nevertheless, updates are needed in certain applications of environmental protection and management principles, including the need for an early warning system for environmental damage and/or degradation and the strengthening of accountability awareness among business actors.